POTENSI BIOGAS DARI CAMPURAN JERAMI PADI DAN KOTORAN AYAM PADA SUHU MESOFILIK DAN TERMOFILIK DENGAN RASIO C/N IDEAL - Gani, M Afdol; Jelita, Marhama (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2025)
This research aims to optimize the utilization of rice straw waste into biogas by mixing chicken manure to achieve an ideal C/N ratio of 30. The method used in the anaerobic fermentation process uses SuperPro Designer software simulation and compares good biogas production from mesophilic temperatures (350C) and thermophilic (550C). The results of the research show that 4,000 kg of rice straw used to achieve a C/N ratio of 30 requires a mixture of 1,455 kg of chicken. Biogas potential from a mixture of rice straw and chicken manure with a C/N ratio of 30 at a temperature of 55°C produces the highest volume of biogas, reaching 617,887 m³, with a methane content of 81.83%. The increase in biogas yield of 20.15% at thermophilic temperatures compared to mesophilic temperatures shows that high temperatures increase the efficiency of biogas production. This research found the potential of rice straw as a sustainable biogas raw material with a C/N ratio of 30 with a thermophilic temperature that influences biogas production and the electrical energy produced.Keywords: Rice Straw, C/N Ratio, Temperature, Biogas